Free Banjari Shalawat Arts Development for Elementary School Children and Teenagers in the Community Environment of Used Goods Managers in Kejagan Village, Trowulan District, Mojokerto Regency - Achmad Muchammad; M. Syahrul Ramadhani (Future Tecno-Science Publisher, 2026)
This community service article describes a free Shalawat Banjari arts-training program for children of Madrasah Ibtidaiyah age and adolescents in Kejagan Village, Trowulan District, Mojokerto Regency. The program was designed as a constructive religious and cultural activity for young people in a recycled-goods management community environment. The activity aimed to strengthen Islamic values, introduce Shalawat Banjari as a local Islamic cultural expression, and improve participants' confidence, teamwork, and basic artistic skills. The program was implemented from 17 June to 13 July 2025 using a participatory approach involving observation, coordination with local religious figures, participant recruitment, routine practice, peer tutoring, audiovisual media, reflection, and a final performance. The core participants documented in the activity consisted of 14 children and adolescents, while broader participation occurred during open practice and community events. The results show improvement in three main aspects: basic vocal and rebana skills, character development through discipline and cooperation, and social participation through the involvement of parents, mosque administrators, youth mosque members, and local religious figures. This program indicates that Shalawat Banjari can serve as an accessible medium for Islamic character education and community-based cultural preservation when supported by continuous mentoring.